PENINGKATAN HASIL BELAJAR INFORMATIKA MELALUI MODEL PEMBELAJARAN WINDOWS SHOPPING PADA MATERI APLIKASI PERKANTORAN DI KELAS VIII C SMP NEGERI 7 MALANG - Al-Jabbar, Habib Muhammad; Irianto, Wahyu Sakti Gunawan; Wardhana, Nyoman Dedi Kusuma; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This Classroom Action Research was conducted as a solution to apply a learning model proven effective in improving Informatics learning outcomes through the implementation of the Windows Shopping learning model. The research was divided into two cycles and carried out in class VIII C of SMP Negeri 7 Malang, involving 32 students. Each cycle consisted of four stages: planning, implementation, observation, and reflection. Data were collected using observation, tests, and documentation techniques. The data were then analyzed quantitatively using descriptive statistics by calculating the N-gain score. The results of this classroom action research show an improvement in student learning outcomes in each cycle. In the first cycle, the average pretest score increased from 54.06 to 73.75 in the posttest, with an average N-gain of 0.43 (medium category). In the second cycle, the average pretest score rose from 63.28 to 87.81 in the posttest, with an average N-gain of 0.67 (medium to high category). The implementation of the Windows Shopping model improved conceptual understanding, active engagement, and collaboration among students. These findings indicate that the Windows Shopping learning model is effective and has a positive impact on project-based Informatics learning in the context of the Merdeka Curriculum.